Fiscal policy with banks and financial frictions - Asimakopoulos, Panagiotis; Asimakopoulos, Stylianos (Journal of Financial Stability, 2019)
We assess the role of banks to the transmission of optimal and exogenous changes in fiscal policy to the economy. We built-up a dynamic stochastic general equilibrium model with patient and impatient agents, banks and a government to find that banks and their associated capital-adequacy constraint mitigate the negative spill-over effects to the economy from higher taxes. Specifically, we confirm that labour income tax is the most distortionary fiscal instrument. The optimal choice of a housing tax is the most favorable funding source to a temporary increase in public spending. The combination of housing and labour taxes is the most preferred tax bundle to be optimally chosen under negative output shocks. Moreover, a permanent increase in housing tax is beneficial if it is welfare enhancing and the existence of banks benefits mainly impatient households under permanently higher consumption taxes. Finally, these results remain robust to various robustness checks.